Medical Student and Primary Care Physician Perception of the Surgical Management of Upper- and Lower-Extremity Peripheral Nerve Entrapment. Issue 5 (May 2016) - Lee, Andy C.H.; Drake, David B.; DeGeorge, Brent R.
Abstract : Background: Upper- and lower-extremity peripheral neuropathies are commonly encountered in the primary care setting and account for 14.3 million specialist referrals in the United States annually. Despite the integral role of plastic surgeons in the development of the field of peripheral nerve surgery, plastic surgeons are not commonly recognized as peripheral nerve specialists. The purpose of this study was to investigate the pattern of diagnosis, treatment, and referral of upper- and lower-extremity peripheral nerve entrapment syndromes by both medical students and primary care providers. Methods: An online survey including 5 peripheral nerve entrapment clinical scenarios (2 upper extremity and 3 lower extremity) was administered to medical students and primary care providers at a large academic medical center. Respondents were surveyed for level of training, prior clinical exposure, initial diagnostic studies of choice, initial therapeutic modalities of choice, need for subspecialty referral, and appropriate surgical subspecialists for management of the peripheral nerve entrapment. Results: Overall, 248 medical students (38.3% response rate) and 54 primary care providers (13.5% response rate) completed the study. The majority of medical students and primary care providers indicated prior clinical experience with upper-extremity peripheral nerve entrapment in contrast to lower-extremity peripheral nerve entrapment with 26.2% and 39.9% of medical students and primary care physicians reporting prior clinical exposure, respectively. Medical students and primary care providers identified orthopedic surgery as the preferred choice for subspecialty referral for both upper- and lower-extremity peripheral nerve entrapment. Primary care physicians are more inclined to initially manage upper-extremity nerve entrapment without referral to other specialties than for the management of lower-extremity nerve entrapment; 38.0% and 61.1% of the primary care physicians surveyed would refer to another specialty for the initial management of carpal tunnel and cubital tunnel syndromes, in contrast to 83.0%, 90.0%, and 88.2% for the management of common peroneal nerve compression, sural nerve compression, and deep peroneal nerve compression, respectively. Conclusions: We contend that early education of medical students and primary care providers regarding the role of plastic surgeons as peripheral nerve specialists may improve future referral patterns. Abstract : Supplemental digital content is available in the text.